The Church – Spirit in the Theology of Tertullian - Vicastillo, Salvador (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The spirit (a stoic category) is the inner substance of Divinity. The Church is essentially a basic part of that spirit, which thickens and materializes its own body. It is in this so-called Church-spirit space that the Holy Trinity appears and woks. It is just three faithful persons that make a church because they possess what is essential in the Church, the spirit. That is, in fact, what makes them become priest (in a secondary order) and confers them the real power to act when the clergy is away. Clergy is involved in ruling the Church and on top of that hierarchy is the Apostle Saint Peter, the Primate. The powers that Jesus Christ conferrer to Peter (disciplina and potestas) were destined to the whole Church, that is, there where the root and foundation. These powers go to the church which is directly related to the bishop.
Keywords: Church; Spirit; Faithful Persons; Powers; Peter